Correlation between coping mechanisms and the burden experienced by caregivers of cancer patients - Zendrato, Mey Lona Verawaty; Sigalingging, Astika Irmawaty; Gunawan, Ni Putu Ika Novita (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Caregivers of breast cancer patients are at risk of experiencing a high caregiver burden due to prolonged physical, emotional, and social demands. Coping responses play an important role in determining how caregivers manage these challenges. Objective: The study aimed to analyze the relationship and caregiver burden in caring for breast cancer patients. Methods: This study employed a quantitative cross-sectional design involving 200 caregivers of breast cancer patients. Inclusion criteria were age ≥18 years, good health status, active involvement in caregiving, and the ability to read Indonesian. Data were collected from August to December 2024 using a demographic questionnaire, the Coping Orientation to Problems Experienced (COPE), and the Indonesian version of the Zarit Burden Interview (ZBI). Data were analyzed using the chi-square test. Most caregivers with maladaptive coping experienced a high caregiver burden (79.8%), while only 20.2% of caregivers with adaptive coping reported a high burden. Results:  Statistical analysis showed a significant association between coping responses and caregiver burden (p = 0.001). Conclusion: Caregivers who used maladaptive coping strategies had a significantly higher likelihood of experiencing a high caregiver burden compared with those who used adaptive coping strategies. Coping responses are significantly associated with caregiver burden among caregivers of breast cancer patients. Strengthening adaptive coping strategies through caregiver-focused interventions is essential to reducing caregiver burden and supporting optimal patient care.